Rupture of esophageal varices due to portal hypertension - Yusri Dianne Jurnalis; Yorva Sayoeti; Marlinda Marlinda (Paediatrica Indonesiana, 2010)
Variceal bleeding is the most common cause of serious upper gastrointestinal (UGI) bleeding in children. Most variceal bleeding is esophageal.1 Hemorrhages from esophageal varices due to portal hypertension are a major cause of morbidity and mortality. There is a 30% mortality rate following an initial episode of variceal hematemesis. Mortality increases to 70% with recurrent variceal hemorrhage. Moreover, the one year survival rate after variceal hemorrhage is often poor (32 to 80%).2-4 We report a case of esophageal varices rupture caused by portal hypertension, an emergent case in the Pediatric Gastrohepatology division.